2011
DOI: 10.1002/cite.201100027
|View full text |Cite
|
Sign up to set email alerts
|

Redispersion Microreactor System for Phase Transfer Catalyzed Esterification

Abstract: Redispersion Microreactor System for Phase Transfer Catalyzed EsterificationAn interdigital mixer -redispersion capillary assembly was applied to prevent the liquid-liquid bubbly flow coalescence in microreactors. The redispersion capillary consisted of 1 mm long and 0.25 mm inner-diameter constrictions placed every 0.50 m along the channel length. The system was tested on the phase transfer catalyzed esterification to produce benzyl benzoate. The application of constrictions to prevent coalescence resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…This is in accordance with the existence of an optimum flow ratio with a maximum productivity as described in the literature [31]. Using CHBr 3 as the solvent instead of CH 2 Cl 2 (Table 1, Entry 16) resulted in lower yields.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…This is in accordance with the existence of an optimum flow ratio with a maximum productivity as described in the literature [31]. Using CHBr 3 as the solvent instead of CH 2 Cl 2 (Table 1, Entry 16) resulted in lower yields.…”
Section: Resultssupporting
confidence: 63%
“…Jovanovic et al [31] successfully used a solution of 45% (w/w) KOH (aq) containing 0.12 wt.% TEBA (aq) for the PTC alkylation of phenylacetonitrile. They found that increasing the AO ratio increased the yield of alkylation product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The saturated bleach had a higher ionic strength, facilitating the extraction of organic salts from the aqueous phase to the organic phase. 36 Given the same residence time, the ratio of the aqueous and organic flow rates (Q A /Q O ) also played an important role in controlling the overall reaction rate as a result of the increase in surface to volume ratio and hence higher mass transfer rate with increasing Q A /Q O 37,30 (see Figure 3b). Since the amount of NaOCl was already in large excess at Q A /Q O = 1:1, the increased rates could be attributed to higher interfacial area, implying that the reaction is within the mass-transfer-limited region.…”
Section: ■ Results and Discussionmentioning
confidence: 99%